Isolation of polyphenols from spent coffee grounds and silverskin by mild hydrothermal pretreatment - Conde, Teresa (2016)
In the present study, a new method for isolation of polyphenols (PP) from spent coffee grounds (SCG) and coffee silverskin (CS) is described. The method consisted in a mild hydrothermal pretreatment at 120 °C, during 20 min, using a liquid to solid ratio of 20 ml/g. PP (determined as gallic acid equivalents, GAE) were the most abundant components in the extracts produced by this method, corresponding to 32.92 mgGAE/gSCG and 19.17 mgGAE/gCS, among of which, flavonoids corresponded to 8.29 and 2.73 mg quercetin equivalents/g of SCG and CS, respectively. Both extracts presented antioxidant activity but the results were higher for SCG extract, probably due to the highest content of PP present. Negligible effects (less than 1% solubilisation) were caused by the hydrothermal pretreatment on cellulose, hemicellulose and protein fractions of these materials. Some minerals elements were present in the extracts, potassium being the most abundant. Hydrothermal pretreatment under mild conditions was demonstrated to be an efficient method to recover antioxidant PP from coffee residues.